(3YbO GdHjYI GdeHGQcI GdSYjOI GdChdi HhdGjI GdYgO dSjOfG hehdGfG CejQ GdeDefjf Yf Cgd bQWHI hCfXGQgG ef GdehMOjf SfI (B588 (3g`s
(3ChdgG (B:s
(3Ef GdMeO ddg fMeOg hfSJYjfg hfSJZaQg hfDef Hg hfJhcd Ydjg s
(3BNQgG (B:s
(3MJi cedJ CSeGA GdMGVQjf ef Cgd GdMGVQI hGdeSJbQjf ef Cgd GdHGOjI hGdMeO ddg QH GdYGdejf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B4s
(3jdjgG fSNI ef GdLhGH Ydi cJGH GdMVQI GdEeGejI CjO Gddg CeQgG hCYR fUQgGhjbY ai (B6 (3hQbGJs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3GdfSNI HgG JdhjK s
Keywords: (3GdJGQjNs